(untitled) (Revista de Ciências Agroveterinárias, 2022)
In a soybean seed production field, the characteristics related to seed quality are not uniform since they were showing variation within the same production area. The work aimed to identify the spatial distribution of yield, quality and storage potential of soybean seeds obtained under tropical lowlands conditions, in the region of Lagoa da Confusão (Tocantins state, North region of Brazil). It used systematic sampling and regular sampling grid with 100x100 m between each point (one point per hectare). At harvest, the plants were threshed with the seeds be cleaned, weighed, dried and stored until the time of physiological and sanitary analyses. They were performed at 50, 100, 150 and 200 days after storage (DAS). Finally, the current soil moisture was also determined when the soybean was harvested. The results had shown that: seed yield varied by 13.03% (195-342 g.m-²); the germination and accelerated aging tests had shown increased variation with storage time, with greater variability (24% to 96%) at 200 DAS; the traits analyzed had shown a strong degree of spatial dependence and with these it possible to identify regions with higher and lower quality of soybean seeds related to vigor and also a greater variation and distinction in the study area according to the period of post-harvest analysis.